2021
DOI: 10.3233/jnd-200611
|View full text |Cite
|
Sign up to set email alerts
|

Improving Care and Empowering Adults Living with SMA: A Call to Action in the New Treatment Era

Abstract: While Spinal Muscular Atrophy (SMA) has historically been managed with supportive measures, the emergence of innovative medicines has given those living with SMA hope for improved quality of life and has revolutionized care. Despite these advances, the use of therapies and changes in disease management strategies have focused on pediatric populations, leaving adults living with SMA, and those transitioning into adulthood, relatively neglected. Through a multi-faceted approach that gathered unbiased perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…5,6,10,26 Until recently, adult SMA patients had been frequently disengaged and neglected from both health services and research studies. [27][28][29] The approval of disease-modifying treatments has resulted in a substantial rise of referrals, and an increasing interest of research in adult SMA patients. 29,30 At present, motor function scales most frequently used in adult SMA patients have been designed and validated in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,10,26 Until recently, adult SMA patients had been frequently disengaged and neglected from both health services and research studies. [27][28][29] The approval of disease-modifying treatments has resulted in a substantial rise of referrals, and an increasing interest of research in adult SMA patients. 29,30 At present, motor function scales most frequently used in adult SMA patients have been designed and validated in children.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] The approval of disease-modifying treatments has resulted in a substantial rise of referrals, and an increasing interest of research in adult SMA patients. 29,30 At present, motor function scales most frequently used in adult SMA patients have been designed and validated in children. However, both populations present considerable differences (e.g., in disease progression rate, contractures and scoliosis, comorbidities, etc.…) that could diversely affect the performance of motor scales.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whenever possible, functional stratification should be considered in studies addressing adult SMA patients. 25,33 Previous studies have reported a 30-60% of responders, according to the predefined MCID of motor scales. 8,11,12 However, the responder rate should also be interpreted with caution, since two important biases could lead to under-and overestimations.…”
Section: Discussionmentioning
confidence: 99%
“…overlooked the particularities of adult SMA patients, characterized by a huge clinical heterogeneity and poorly defined natural history. 25,26 Recently, the first reports of real-world evidence on the efficacy and safety of nusinersen in adult SMA patients have been published. [8][9][10][11][12][13][14] Most of them, but not all, 10 suggest nusinersen efficacy, at least in a subset of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation